Correlation between structural and electronic order-disorder effects and optical properties in ZnO nanocrystals - La Porta, F. A. [UNESP]; Andres, J.; Vismara, M. V. G. [UNESP]; Graeff, Carlos Frederico de Oliveira [UNESP]; Sambrano, Julio Ricardo [UNESP]; Li, M. S.; Varela, José Arana [UNESP]; Longo, E. [UNESP] (Royal Soc Chemistry, 2014)
The correlation between structural and electronic order-disorder effects in understanding the optical properties of flower-like ZnO nanocrystals synthesized by the microwave-assisted hydrothermal method at low temperatures and short times is discussed. Theoretical simulations were performed at the density functional theory level to gain a better understanding of the experimental data from X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), electron paramagnetic resonance (EPR), ultraviolet-visible diffuse reflectance (UV-vis) spectroscopy and photoluminescence (PL) measurement studies at different temperatures. The decrease in band gap values is due to the presence of intermediate states above the conduction band. These discrete levels are formed by structural and electronic disorder of tetrahedral [ZnO4] clusters which enhance the electron-hole pair.